The species concept in Zubiri: Contributions to the contemporary debate about the ontological species problem - Vargas, Esteban (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
In this paper we try to show Zubiri’s concept of species as an essential moment of the individual and how this concept is in contrast to other species concepts present in the current debate, for example, species understood as class, population and historical individual. We propose that this essentialist concept of species is not incompatible with the current idea of evolution.